Direct percutaneous endoscopic jejunostomy tube placement in patients post Roux-en-Y gastric bypass, a single tertiary care center experience - Aryan, Mahmoud; Colvin, Tyler; Mulki, Ramzi; Daley, Lauren; Patel, Parth; Locke, John; Ahmed, Ali M.; Kyanam Kabir Baig, Kondal R.; Mönkemüller, Klaus; Peter, Shajan (Endoscopy International Open, 2022)
Background and study aims Obesity prevalence continues to rise in the United States with Roux-en-Y gastric bypass (RYGB) surgery being one of the most common bariatric procedures. With this trend, more patients with altered upper gastrointestinal (UGI) anatomy have required endoscopic intervention including direct percutaneous endoscopic jejunostomy (DPEJ) placement. We aimed to assess the safety and success rates of DPEJ in RYGB patients.Patients and methods All patients at a tertiary care referral center who underwent DPEJ during an 8-year period were queried from a prospectively maintained registry of all enteroscopy procedures. Duplicate cases and altered upper UGI anatomy subtypes other than RYGB were excluded. The final cohort consisted of two groups: RYGB vs native anatomy (NA). Demographic, procedural, readmission, follow-up, and complication data were recorded. Comparative analysis was performed.Results Seventy-two patients were included where 28 had RYGB and 44 had NA. Both groups had similar baseline and pre-procedure data. Procedure success rate was 89 % in RYGB patients and 98 % in NA patients (P = 0.13). There were no intraprocedural complications. Early and late postprocedural complication rates were similar between the groups (both 4 % vs 7 %). Average follow-up times in the RYGB and NA groups were 12.97 ± 9.35 and 13.44 ± 9.21 months, respectively. Although readmission rates at 1 and 6 months were higher in the NA versus the RYGB group (21 % vs 7 % and 25 % vs 15 %), these differences were not significant.Conclusions DPEJ can be successful and safely placed in RYGB patients with no significant difference in procedure success, complication, or readmission rates when compared to control.